(untitled) (American Journal of Technology and Applied Sciences, 2025)
The optimization of open channel flows remains a cornerstone of efficient water resources management, particularly in the context of climate variability, increased demand for irrigation, and ecological sustainability. This paper investigates the application of modern computational techniques, including Computational Fluid Dynamics (CFD), Artificial Intelligence (AI), and ecohydraulic modeling, to enhance the hydraulic performance of open channels while preserving aquatic habitats and ecological integrity. The study emphasizes the integration of hydraulic efficiency with ecological considerations—a synergy that is critical in contemporary engineering. It combines numerical simulation, flow profiling, and habitat modeling across various channel geometries, substrate conditions, and environmental flow scenarios. Case studies from semi-arid regions, including Central Asia, demonstrate the practical benefits of using hybrid models for optimal flow distribution, energy dissipation, and sediment transport control. The paper concludes with strategic guidelines for implementing computationally-driven hydraulic optimization in environmentally sensitive areas, thus supporting sustainable infrastructure development and water resource governance.